Intermediate Algebra (6th Edition)

Published by Pearson
ISBN 10: 0321785045
ISBN 13: 978-0-32178-504-6

Chapter 7 - Section 7.3 - Simplifying Radical Expressions - Exercise Set: 46

Answer

$y\sqrt[3] (y^{2})$

Work Step by Step

$\sqrt[3] (y^{5})=\sqrt[3] (y^{3}\times y^{2})=\sqrt[3] (y^{3})\times\sqrt[3] (y^{2})=y\sqrt[3] (y^{2})$ We know that $\sqrt[3] (y^{3})=y$, because $(y)^{3}=y^{3}$.
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.